Pengujian Kadar Pengawet Asam Benzoat dan Asam Sorbat Pada Permen Keras Menggunakan Kromatografi Cair Kinerja Tinggi - Reizza Muhammad Giyats Al Hisyam Dwi Samara; Nuning Yuningsih; Nezly Nurlia Putri (Jurnal Teknologi dan Mutu Pangan, 2023)
Hard candy is a type of solid snack made from sugar or a mixture of other sweeteners with or without the addition of other food ingredients and food additives (BTP). Based on the BPOM Regulation No. 11 of 2019 concerning BTP, the use of benzoic acid in hard candy is a maximum of 500 mg/kg body weight while sorbic acid is a maximum of 1000 mg/kg body weight. Excessive consumption of benzoic acid and sorbic acid can endanger health. Food quality control of the use of BTP can be done by routine testing in the laboratory. One of the instruments that can detect BTP is High Performance Liquid Chromatography (HPLC). This study aims to analyze the levels of benzoic acid and sorbic acid in hard candy samples using HPLC instrument. The results of the analysis of benzoic acid and sorbic acid levels in hard candy samples showed that both were not detected by the detector. The LOD value of benzoic acid obtained on HPLC instrument was 4.92 mg/kg and the LOD of sorbic acid was 3.70 mg/kg) which limits its use to meet BPOM regulation No. 11 of 2019. The testing process for benzoic acid and sorbic acid in hard candy samples is also correct and in accordance with the procedure, where the recovery value is in the range of 90-107%, the RPD value is smaller than the 2/3 CV Horwitz value (In benzoic acid, the RPD value is 1.02% and the CV Horwitz value is 6.42 while in sorbic acid the RPD value is 0.75% and the CV Horwitz value is 4.15) with a correlation coefficient that meets the linearity (r) requirement of 0.9999.